기장군 농업·농촌발전 종합계획연구 - 박문호 (한국농촌경제연구원, 2006)
Currently, the world is the opening of agricultural markets driven by WTO/DDA negotiations, conclusion of FTAs between countries and changes of agricultural policies in a way that places the focus on the multilateral functions of agriculture. These global changes in the agricultural prospect are having a huge impact on the domestic agriculture and agricultural administration, and ripple effects are predicted on the local agricultural sectors. In particular, investment and interest of the local autonomous entities in agriculture constitute a major factor in determining the quality of life in the farming community, competitiveness of each farm's production and income level of households. In this regard, formulation of agricultural plans and implementation of plans by the local autonomous entities are gaining increasing significance. In this study, in-depth examinations are done on regional, environmental and socio-economic traits regarding agriculture and rural communities of the overall Gijang-gun each town and Myeon in viewpoint of internal and external environments of agriculture and rural communities of Gijang-gun. Also, to come up with inclusive development plans for the agriculture and rural communities by assessing strong and weak points is the primary goal of this study. Comprised of four Myeons & two town, Gijang-gun, the region could be mention a city and rural composite county as it sits near consuming cities like a suburb region around a metropolis. By sectors, the rice grown in the regional stands a better chance to be promoted as a specialized premium brand as the eco-friendly rice cultivation complex was already in place. However, when it comes to dissemination of superior breeds and processing systems, the region lags behind. Regional specialized crop is pears. Recently, the production of horticulture has been increasing, but the cultivation of these vegetables is on a small-scale. From the front of view of livestock farming, Korean beef cattle stands out in Gijang-gun. For this reason, the region is now under the process of being designated as 'Special Roast Korean Beef Cattle Zone in Cholma.' However, the continued rise of the land prices in the region faces difficulties in realizing economy of scale in livestock industry and newly entering the sector. In the case of the distribution of the agricultural produce, the region is not suitable for the function of a place of production, In the meantime, Gijang-gun is blessed with abundant wonderful natural landscapes and tourism resources which consists of rural communities, mountain and fishing villages. Nevertheless, only a handful of farm households are participating in rural communities tourism projects utilizing these rich resources. Living standards of rural communities are quite good on average in the region compared to other parts of the country. In addition, the community is actively engaged in sisterhood relationships with adjacent businesses, and many employment opportunities are characterized in other sectors than agriculture. Given the current status, positively needed for Gijang-gun is the construction of "Well-being Town" for the sake of further development of agriculture and rural communities. In order to realize the vision of "Well-being Town", what should be done is as follows: construction of high-quallity eco-products system, development of high-income item for agricultural products, activating of item organization of agricultural products, supporting of public information and marketing for agricultural products, re-construction of a pleasant living environment and rest space.